The Negative Influence of the Technical Means on Children's Development - S. Luparenko (University of Sofia, 2014)
The negative impact of the technical means (computer, TV) on children's development is characterized. This negative impact means damage of physical and mental health; lack of positive moral-ethic influence, forming a soulless, spiritless person; children's detachment from real life and their impossibility to realize themselves; increased aggressiveness; disappearance of the components of children subculture; availability (in virtual world) of the information which can influence child's development negatively; children's dependence on computer games, Internet-addiction, etc. The recommendations for parents to reduce the negative influence of technical means on children are given.